2013
DOI: 10.1007/s10072-013-1381-1
|View full text |Cite
|
Sign up to set email alerts
|

Onabotulinum toxin A for treatment of chronic migraine with medication overuse

Abstract: Chronic migraine is a common and debilitating headache syndrome. Botulinum neurotoxin (BoNT), a potent toxin produced by the anaerobic bacterium Clostridium botulinum, used largely for treatment of disorders associated with increased muscle tone and hyperidrosis, has been recently used for patients suffering from chronic migraine. In this study, two groups of patients were treated with different dosages of BoNT A to verify the efficacy for chronic migraine. The results confirmed the efficacy of BoNT A when use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…A similar beneficial effect was observed in patients with coexistent MOH. As such, our results, overall, are in agreement with previously published studies applying similar study design in patients with or without MOH [ 13 17 , 23 – 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A similar beneficial effect was observed in patients with coexistent MOH. As such, our results, overall, are in agreement with previously published studies applying similar study design in patients with or without MOH [ 13 17 , 23 – 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The main limitation of our study was the relatively high percentage of early drop-outs before T3 ( n = 38; 32 %) from the initial cohort of 119 patients enrolled. Even so, the sample size of our efficacy population ( n = 81) was larger compared to other studies with similar design [ 13 16 ]. Moreover, ITT analysis also favoured Onabotulinumtoxin-A treatment in the current setting.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A study analyzing long-term experience with OBOT-A in CM demonstrated that after an average of two years treatment with OBOT-A in responder CM patients the need for acute pain medication was decreased by 53% and emergency visits were reduced by 61% [ 77 ]. In a recent clinical trial, CM patients with medication overuse were studied after a five-day-long withdrawal period with 150 U OBOT-A injection, which confirmed the efficacy of OBOT-A [ 78 ]. Results of another clinical study in which OBOT-A was used in the dose of 155 U, in accordance with the PREEMPT study protocol, showed that the number of headache days per month and the acute medication intakes decreased significantly in the treatment group [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the nerve-block procedure and botulinum toxin type A (BTX-A) injection can be beneficial for treating primary headache disorder [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. BTX-A is routinely administered as a treatment for chronic migraine in the frontal region [ 9 , 13 , 15 ]. The trigger point is generally targeted as the injection site for the BTX-A treatment to relieve the associated pain [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%